Faktor-Faktor Yang Mempengaruhi Pemilihan Karir Menjadi Akuntan Publik Oleh Mahasiswa Akuntansi Pts Se-Surakarta - Kurniawati, Alfiana; , Drs. Suyatmin Waskito Adi, M.Si (2016)
This study aims to analysis apakah the financial reward factor, professional training, professional recognition , social values, work environment, labor market considerations, and personality of students influence the selection of a public accounting career. Population in this research are student in Muhammadiyah Uniersity of Surakarta and Islamic Batik University. To colect the sample, it use convenience sampling method. The sample that use in this reasearch about 166 respondents. In this research, to analize data used multiple regression analysis. The result of this research show that R2 equal to 0,514 it means that 51,4% students influence the selection of a public accounting career are based on the financial reward factor, professional training, professional recognition , social values, work environment, labor market considerations, and personality. And for the 48,6% are based on out of variable models. The result of t test show that the financial reward factor, professional training, professional recognition, social values, work environment, labor market considerations, students influence the selection of a public accounting career has influence to the career selection to be public accountant.